2021
DOI: 10.1186/s12879-021-05908-z
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life of HIV-infected individuals: insights from a study of patients in Kermanshah, Iran

Abstract: Background Quality of life (QOL) is one of the major factors to assessing the health and wellbeing of People living with HIV (PLWH). Likewise, improved QOL is among the prominent goals of patient treatment. This study was conducted to investigate the QOL of PLWH in Kermanshah, Iran. Methods This cross-sectional study was conducted on 364 PLWH of Kermanshah between 2016 and 2017. Outpatients were selected as the sample through the convenience sampli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 52 publications
1
17
1
Order By: Relevance
“…Our ndings also indicate that the highest mean difference scores were reported in the psychological domain for both A. annuaarm (15.7, p = 0.003) and A.annua + M.oleifera (29.02, p < 001). These ndings are in line with previous studies [31,33,34], and the ndings provide a useful assessment of how PLWH participants' lives are affected by treatment interventions. The high psychological score may also generally play into [35] improved mental health, adherence to treatment, higher immune response to HIV infection, and well-being of individuals.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our ndings also indicate that the highest mean difference scores were reported in the psychological domain for both A. annuaarm (15.7, p = 0.003) and A.annua + M.oleifera (29.02, p < 001). These ndings are in line with previous studies [31,33,34], and the ndings provide a useful assessment of how PLWH participants' lives are affected by treatment interventions. The high psychological score may also generally play into [35] improved mental health, adherence to treatment, higher immune response to HIV infection, and well-being of individuals.…”
Section: Discussionsupporting
confidence: 90%
“…Health-related QoL is increasingly recognized as an important outcome in randomized trials [30] because it provides valuable information to assess the health status and well-being of PLWH [31,32]. We observed a signi cant improvement in the reported QoL, with signi cant mean differences between the baseline and 12-month scores observed in the physical, social and psychological domains of the WHOQOL-BREF tool for both individuals using A. annua and M. oleifera (Table 4).…”
Section: Discussionmentioning
confidence: 75%
“…1 There is no cure for this disease, and to date, 36.3 million people have died from this disease. 2 However, with increasing awareness of methods of prevention, diagnosis, treatment, and patient care, HIV has become a chronic controllable disease that allows infected people to live long, healthy lives. 3…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have also reported factors associated with good QoL of PLHIV, such as being employed, having no financial concerns, not having mental health issues (e.g., stress, depression, anxiety) and other medical comorbidities, higher education level, and undergoing ART. 8,10,14,17,18 Other supporting factors for good QoL of PLHIV include the availability of social support, including emotional, tangible, and informational support, and having good coping strategies towards HIV-related difficult life situation. 19,20 Similarly, studies with MSM living with HIV have reported that their better acceptance of the illness, family acceptance and peer support are positively associated with their better QoL.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] The use of illicit drugs which negatively influence the physical and mental well-being of PLHIV was also found to cause poor QoL among them. 14 Stigma, perceived discrimination, adverse effects of ART, non-adherence to ART low family income are factors associated with poor QoL among men who have sex with men (MSM) living with HIV 15,16 .…”
Section: Introductionmentioning
confidence: 99%